INSILICO DESIGN, SYNTHESIS AND CHARACTERIZATION OF SOME NOVEL BENZOTHIAZOLE DERIVATIVES AS ANTI-CANCER AGENTS - Pappachen, Leena K; Zachariah, Subin Mary; Chandran, Deepthy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Cancer is a disease characterized by uncontrollable, irreversible, independent, autonomous, uncoordinated and relatively unlimited and abnormal over growth of tissues. Breast cancer is the second most common type of cancer after lung cancer. The aim of the study is to carry out the docking studies, synthesis and anti-tumour activitiesÂ of Benzothiazole derivatives containing oxadiazole groups or amino groups. Methods: The docking studies of benzothiazole derivatives were done with known anti-cancer targets like oestrogen receptor by using argus lab and auto dock programmes with the standard drug tamoxifen. Based upon Â the results obtained from the molecular modeling, the derivatives were selected for the synthesis. The synthesized compounds were characterized by melting point, TLC, IR, 1H NMR, 13CNMR, MASS spectral data and screened for their in- vitro anti-cancer activities. Results: The docking scores obtained for benzothiazole derivatives (BT1,BT2,BT3,BT4) and std.tamoxifenÂ from the preliminary docking program by using Â argusLabÂ were- 9.68, -9.4,-9.59, -11.1988,-9.71 and Â by using autodock program were -6.29, -5.25,-7.19,-7.48,-3.86 Â respectively. All the four derivatives were synthesized, characterized and subjected to in vitro anticancer screening by MTT assay in breast cancer (MCF-7) cell lines. Compounds DBT1, DBT2, DBT3 were the most active compounds against MCF-7 cell lines with IC50 of 70.0, 64.0 and 65.0, respectively. Conclusion: All the fourÂ derivatives showÂ good docking scores when compared to standard drug and can be concluded that all the synthesized benzothiazoleÂ ligands show good anti-cancer property. Keywords: Benzothiazole, Oxadiazole, Estrogen receptor, Anticancer targets.